Measuring College and University Dining Services Directors’ Knowledge, Attitudes, Challenges, and Implementation of Sustainable Development - Zhou, Ying (Kansas State University, 2010)
Today, the rapid development of modern science and technology has allowed humans to use many of these technological conveniences to improve daily life. At the same time because of these improvements and population growth, humans are facing serious challenges of global warming, overrun of solid waste materials and environmental pollutants, natural resource depletion, biodiversity loss, decreased air quality, increase in acid rain, ozone depletion and many other critical environmental issues which need urgent solutions to avoid long-term and irreversible damages to our climate (Goodland, 1995; Hedin & Likens, 1996; and Last, 1993). Along with the increasing rate of environmental challenges and large quantities of energy demands many have begun to be concerned about the environment and relate to it as the “Going Green” movement (Dale & Stuart, 2001, and Pyle, 2008). As a result, strategies for sustainable development are being adopted by governments, institutions, operations, and individual households (Citizens United for Renewable Energy and Sustainability [CNRES], 2006). Because sustainability is defined as using methods, materials, and systems that will not deplete resources and has a zero or a positive impact on the environment (Rosenbaum, 1993), the concept of sustainability has begun to gain momentum in various functions and activities in the hospitality and tourism industries (Micheal, 1999). Many of the sustainable strategies implemented in hospitality have been to: (1) protect the environment, (2) provide better ways to meet customers’ needs through “green” operations, (3) cut down waste and costs, (4) increase environmental related governmental policies and regulations, (5) gain more competition power for “green” markets, (6) boost employee morale, (7) limit risks, and (8) build a strong reputation and public relations (Morgan, 2007, and Enz & Siguaw, 1999). Many colleges and universities have joined this sustainability effort by participating in the green campus competition. By doing so, more schools are taking action on sustainability measures reflecting increasing concern about the environment (Sustainable Endowments Institute [SEI], 2008). Kelly (2003), a NACUFS guest director, stated that the first step in starting a green dining services program is to understand what sustainability is and is not. Many dining services directors may have heard about sustainability, yet can they apply their knowledge to developing practical outcomes and solutions? To date, this knowledge has not been measured for managers of college and university services and research is needed to determine their current knowledge, attitudes, challenges and implementation about sustainability (Aber & Mallory, 2009). The primary purposes of this study are to determine what college and university foodservice directors know about sustainability, what are their attitudes about sustainability, what sustainable programs have been implemented in their operations and what are the challenges to implementing a sustainable program in their facilities. A secondary purpose would be to determine differences in sustainability by age of foodservice director, number of meals served and area of the country. The population (n = 2,936) for this study will be members of National Association of College & University Food Services (NACUFS) directors, who have e-mail addresses which listed in the NACUFS 2009 Membership Directory. Members in the directory can be sorted by membership regions: Continental (n=261), Northeast (n=394), Mid-Atlantic (n=737), Midwest (n=524), Pacific (n=460), and Southern (n=560). An instrument will be developed based on previous research and focus group input. An online survey using the Axio system will be e-mailed to the directors. The online letter will introduce the instrument, the research goals, and provide a timeframe for completion. A response rate of 20% (n = 577) is desired to conduct statistical analysis. The data will be analyzed using SPSS version 16.0 (correlation analysis and regression analysis).
Keywords: Colleges; Universities; Foodservice; Sustainability; Dining services